LEVEL OF KNOWLEDGE OF TAXATION, QUALITY OF FISKUS SERVICES, AND PROVISION OF TAX SANCTIONS ON TAXPAYER COMPLIANCE WITH MSME - Nikma Yucha; Rezki Bachtiar Yuliansyah; Rizqa Melia (Ecopreneur.12, 2023)
This research is aimed at proving and analyzing the effect of the level of knowledge of taxation, the quality of tax services, and the imposition of tax sanctions on the taxpayer compliance of MSME actors partially and simultaneously with the MSME research object in Taman Subdistrict, Sidoarjo Regency. They are using quantitative research methods with multiple linear regression analysis techniques. The number of samples that met the criteria for purposive sampling in Taman Subdistrict SMEs was 40 MSME actors. Still, there was a data transformation by adding a sample of 8 MSME actors. The study's results partially examine the quality of tax authorities and the imposition of tax sanctions has a positive and significant effect on taxpayer compliance. At the same time, knowledge of taxation does not positively and significantly affect taxpayer compliance. In simultaneous research, the variables of knowledge of taxation, quality of tax service and imposition of tax sanctions have a positive and significant effect on taxpayer compliance.